2017
DOI: 10.1016/j.idcr.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and diagnosis of acute Q fever in Portugal — A case series

Abstract: Q fever is a worldwide zoonotic infection caused by the obligate intracellular bacterium Coxiella burnetii that can course with acute or chronic disease.This series describes 7 cases of acute Q fever admitted in a Portuguese University Hospital between 2014 and 2015.All cases presented with hepatitis and had epidemiological history. Diagnosis was done by PCR on majority (5) and by serology and PCR in only 2.Serological tests can be negative in the initial period of the disease. Molecular biology methods by pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
4
0
1
Order By: Relevance
“…Q fever was considered due to inadequate clinical response to non-specific antibiotic treatment. Although Yeşilyurt et al [17] acute hepatitis doxycycline Recovery Köse et al [18] headache + splenomegaly ampiciline/sulbactam and ciprofloxacine…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Q fever was considered due to inadequate clinical response to non-specific antibiotic treatment. Although Yeşilyurt et al [17] acute hepatitis doxycycline Recovery Köse et al [18] headache + splenomegaly ampiciline/sulbactam and ciprofloxacine…”
Section: Resultsmentioning
confidence: 99%
“…Close contact with cattle, goats or sheeps suggested aerosol transmission of Q fever. Although compatible epidemiological history is very important in the diagnosis, unfortunately, the importance of animal contact can be ignored by the patients (18). So, this important diagnostic clue should be investigated in detail by the physicians.…”
Section: Discussionmentioning
confidence: 99%
“…While considered to remain unaltered, Q fever prevalence in the human population of Portugal is conflicting with European data that shows a clear increase in cases (DGS, ; ECDC, ). Although little is known regarding Q fever in Portugal, a few recent case reports in humans have been linked to animals, highlighting the concern for zoonotic transfer from ruminants (Alves et al., ). It is therefore of the upmost importance to provide results on the circulation of C. burnetii in sheep, so as to implement measures on animal health and control the disease spread to the human population.…”
Section: Resultsmentioning
confidence: 99%
“…In Portugal, only one wild mammal molecular prevalence study has been performed, but red deer and wild boar were negative to C. burnetii [ 6 ]. Other studies performed in Portugal have reported Q fever in domestic ruminants [ 6 , 37 , 38 , 39 , 40 ], dogs and cats [ 41 ], and humans [ 42 , 43 , 44 , 45 ]. Nevertheless, this study is the first report of C. burnetii antibodies in red deer and wild boar in east–central Portugal.…”
Section: Discussionmentioning
confidence: 99%